Partitioning POMDPs for multiple input types, and their application to dialogue managers - COWDEROY, GRACE (Trinity College Dublin. School of Computer Science & Statistics. Discipline of Computer Science, 2018)
This research looks at the POMDP models used for dialogue management within Spoken Dialogue Systems (SDS). In particular, it examines the difficulty of handling multimodal inputs. It proposes a generalisation of the POMDP model in order to tackle this. This model is shown, via a Car Advisory system, to improve tractability for multimodal inputs.
APPROVED
Keywords: partitioning POMDPs; car advisory system; POMDP; dialogue manager; multimodal input